2022
DOI: 10.3390/ijms23137087
|View full text |Cite
|
Sign up to set email alerts
|

Fibroblast Growth Factor 7 Suppresses Fibrosis and Promotes Epithelialization during Wound Healing in Mouse Fetuses

Abstract: Adult mammalian wounds leave visible scars, whereas skin wounds in developing mouse fetuses are scarless until a certain point in development when complete regeneration occurs, including the structure of the dermis and skin appendages. Analysis of the molecular mechanisms at this transition will provide clues for achieving scarless wound healing. The fibroblast growth factor (FGF) family is a key regulator of inflammation and fibrosis during wound healing. We aimed to determine the expression and role of FGF f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 18 publications
(23 citation statements)
references
References 30 publications
0
23
0
Order By: Relevance
“…In this study, according to RNA-seq results, we found that FGF ( fgf7 ) and the Jak-STAT signalling pathway ( il20ra, il13ra1 ) were upregulated after treatment with Nano-Se@S-induced tissue regeneration. The importance of these two signalling pathways has been stressed in zebrafish and mouse studies [ 54 , 55 ]. Thus, our results are consistent with those of previous investigations.…”
Section: Resultsmentioning
confidence: 99%
“…In this study, according to RNA-seq results, we found that FGF ( fgf7 ) and the Jak-STAT signalling pathway ( il20ra, il13ra1 ) were upregulated after treatment with Nano-Se@S-induced tissue regeneration. The importance of these two signalling pathways has been stressed in zebrafish and mouse studies [ 54 , 55 ]. Thus, our results are consistent with those of previous investigations.…”
Section: Resultsmentioning
confidence: 99%
“…Growth factors in the FGF family have been extensively studied in wound healing pathways, making the significant upregulation of FGF2 and FGF7 of particular note. Growth factors encoded by these genes have been recognized for their promotion of keratinocyte re-epithelialization of wounds as well as anti-scarring and anti-fibrotic effects mediated by inhibition of TGF-β2 and α-SMA, 67 potentially suggesting a contribution from FGF modulation to some of the trends observed in ELISA and immunostaining analyses of these factors. Scarless healing associated collagen 3 was only upregulated in the Q-peptide group, with collagen 5 which promotes dermis/epidermis association.…”
Section: Discussionmentioning
confidence: 99%
“…Our studies also showed that PGF2 α injection slightly elevated and then reduced the expression of FGF7 mRNA. Although little is known about FGF7 in the ovary, it was shown to suppress fibrosis and reduce scarring in a wound healing study [85]. Thus, elevations in FGF2 expression and reductions in FGF7 and FGF12 in response to PGF2 α may serve to coordinate matrix remodeling during luteal regression.…”
Section: Discussionmentioning
confidence: 99%